The impact of aggregation on the photophysics of spiro-bridged heterotriangulenes - Krug, Marcel; Wagner, Maximilian; Schaub, Tobias A.; Zhang, Wen-Shan; Schüßlbauer, Christoph; Ascherl, Johannes D. R.; Münich, Peter W.; Schröder, Rasmus R.; Gröhn, Franziska; Dral, Pavlo O.; Barbatti, Mario; Guldi, Dirk M.; et al. (Angewandte Chemie. International edition, 2020)
We report on the impact of the central heteroatom on structural, electronic, and spectroscopic properties of a series of spirofluorene-bridged heterotriangulenes and provide a detailed study on their aggregates. The in-depth analysis of their molecular structure by NMR spectroscopy and X-ray crystallography was further complemented by density functional theory calculations. With the aid of extensive photophysical analysis the complex fluorescence spectra were deconvoluted showing contributions from the peripheral fluorenes and the heteroaromatic cores. Beyond the molecular scale, we examined the aggregation behavior of these heterotriangulenes in THF/H2O mixtures and analyzed the aggregates by static and dynamic light scattering. The excited-state interactions within the aggregates were found to be similar to those found in the solid state. A plethora of morphologies and superstructures were observed by scanning electron microscopy of drop-casted dispersions.